Multitarget Activities of Müller Glial Cells and Low-Density Lipoprotein Receptor-Related Protein 1 in Proliferative Retinopathies - Sanchez, Maria Cecilia (2022)
Müller glial cells (MGCs), the main glial component of the retina, play an active role in retinal homeostasis during development and pathological processes. They strongly monitor retinal environment and, in response to retinal imbalance, activate neuroprotective mechanisms mainly characterized by the increase of glial fibrillary acidic protein (GFAP). Under these circumstances, if homeostasis is not reestablished, the retina can be severely injured and GFAP contributes to neuronal degeneration, as they occur in several proliferative retinopathies such as diabetic retinopathy, sickle cell retinopathy and retinopathy of prematurity. In addition, MGCs have an active participation in inflammatory responses releasing proinflammatory mediators and metalloproteinases to the extracellular space and vitreous cavity. MGCs are also involved in the retinal neovascularization and matrix extracellular remodeling during the proliferative stage of retinopathies. Interestingly, low-density lipoprotein receptor-related protein 1 (LRP1) and its ligand α2-macroglobulin (α2M) are highly expressed in MGCs and they have been established to participate in multiple cellular and molecular activities with relevance in retinopathies. However, the exact mechanism of regulation of retinal LRP1 in MGCs is still unclear. Thus, the active participation of MGCs and LRP1 in these diseases, strongly supports the potential interest of them for the design of novel therapeutic approaches. In this review, we discuss the role of LRP1 in the multiple MGCs activities involved in the development and progression of proliferative retinopathies, identifying opportunities in the field that beg further research in this topic area. Summary Statement MGCs and LRP1 are active players in injured retinas, participating in key features such as gliosis and neurotoxicity, neovascularization, inflammation, and glucose control homeostasis during the progression of ischemic diseases, such as proliferative retinopathies.